2010
DOI: 10.1007/s11182-010-9456-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic magnetic characteristics of a composite polymeric material based on carbonyl iron

Abstract: Keywords: wicrowave absorbing materials and coatings, composite materials, magnetic permeability and dielectric permittivity spectra, reflection coefficient, microwave range.Nowadays microwave radiation is used not only in special means: consumer devices of high-frequency radio electronics move actively ahead, including mobile telephones, computers, and photo-and videocameras. Due to mastering of gigahertz frequencies, miniaturization, small weight, and high speed of modern hardware is provided. Active masteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The rather narrow operating frequency band is disadvantage of such RAC. It is shown in [5] [6] that double-layer RAC is more broadband and has less reflection coefficient than singlelayer RAC [1]- [3] [7]- [10]. The first layer of such RAC is an absorbing layer.…”
Section: Introductionmentioning
confidence: 99%
“…The rather narrow operating frequency band is disadvantage of such RAC. It is shown in [5] [6] that double-layer RAC is more broadband and has less reflection coefficient than singlelayer RAC [1]- [3] [7]- [10]. The first layer of such RAC is an absorbing layer.…”
Section: Introductionmentioning
confidence: 99%
“…Composite RAM whose matrix is formed by high-molecular polymer compounds and whose fillers are particles of ferro-or ferrimagnetic materials have found wide application [2]. These materials deposited on metal surfaces are effectively used as absorbers of electromagnetic waves.In [3][4][5][6] it was suggested to use carbonyl iron (FeC) powders for RAM in the microwave range. Investigations of the spectra of complex magnetic permeability ( i ′ ′′ μ = μ − μ ) and dielectric permittivity ( i ′ ′′ ε = ε − ε ) of composites with different filling factors at frequencies up to 18 GHz have demonstrated that these materials possess noticeable magnetic and dielectric losses and are promising for application as absorbers of electromagnetic waves in the microwave range.…”
mentioning
confidence: 99%
“…Investigations of the spectra of complex magnetic permeability ( i ′ ′′ μ = μ − μ ) and dielectric permittivity ( i ′ ′′ ε = ε − ε ) of composites with different filling factors at frequencies up to 18 GHz have demonstrated that these materials possess noticeable magnetic and dielectric losses and are promising for application as absorbers of electromagnetic waves in the microwave range. It has also been demonstrated that the two-layer RAM have smaller reflection coefficient and wider frequency band [4,6] in comparison with single-layer RAM [5]. They consist of a strongly absorbing layer deposited on the metal surface and a layer that matches the electromagnetic wave absorber with the free space having smaller values of the magnetic permeability and dielectric permittivity.…”
mentioning
confidence: 99%
See 2 more Smart Citations